2021
DOI: 10.1029/2021jg006247
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Face of Winter: Lessons and Questions From the Laurentian Great Lakes

Abstract: Among its many impacts, climate warming is leading to increasing winter air temperatures, decreasing ice cover extent, and changing winter precipitation patterns over the Laurentian Great Lakes and their watershed. Understanding and predicting the consequences of these changes is impeded by a shortage of winter-period studies on most aspects of Great Lake limnology. In this review, we summarize what is known about the Great Lakes during their 3-6 months of winter and identify key open questions about the physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 190 publications
(356 reference statements)
0
28
0
Order By: Relevance
“…A traditional narrative that these ecosystems are ‘dormant’ during winter has been repeatedly challenged in recent years. Notably, some recent work has demonstrated that pelagic primary production continues under lake ice, especially in temperate regions where levels of sunlight remain sufficient to fuel plankton growth (Hampton et al ., 2017; Ozersky et al ., 2021). Our data provide further support for this, highlighting how pelagic specialist DR whitefish can survive winter, albeit with extreme impacts to their body condition, while occupying an almost exclusively pelagic niche.…”
Section: Discussionmentioning
confidence: 99%
“…A traditional narrative that these ecosystems are ‘dormant’ during winter has been repeatedly challenged in recent years. Notably, some recent work has demonstrated that pelagic primary production continues under lake ice, especially in temperate regions where levels of sunlight remain sufficient to fuel plankton growth (Hampton et al ., 2017; Ozersky et al ., 2021). Our data provide further support for this, highlighting how pelagic specialist DR whitefish can survive winter, albeit with extreme impacts to their body condition, while occupying an almost exclusively pelagic niche.…”
Section: Discussionmentioning
confidence: 99%
“…This rudimentary state of scientific understanding of H. alternans overwintering is generally consistent with that of the winter biology of most of the benthic organisms of the Great Lakes. This is particularly true of the winter life on the bottom of Lake Superior, which remains largely unexplored [ 74 ]. Based on the general observations made over the past two decades, the surf zone habitat in our research area is typically ice-free into January.…”
Section: Discussionmentioning
confidence: 99%
“…Lake Erie’s winter phytoplankton blooms have been documented for decades ( 1 ), and recent studies have revealed that these communities are dominated by centric, colonial diatoms, including Aulacoseira islandica and Stephanodiscus binderanus ( 2 4 ). However, the ecophysiology of these blooms and comprehensive analyses of the winter community have received limited attention ( 5 ).…”
Section: Announcementmentioning
confidence: 99%